Measuring social determinants influencing Australian university students’ completion: confirmatory factor analysis - Pham, Thu D.; Baeza Penã, Angela; Xing, Congcong; Blue, Levon E.; Anderson, Peter J.; Chappell, Rhetta (Frontiers in Education, 2025)
IntroductionThis study compares the 5-factor and 4-factor models of the Higher Education Success Factor (HESF) framework. Through this research, we aimed to identify the social determinants influencing Australian university students’ completion rates. We analysed responses from 2,248 participants. The social determinants we examined included the social environment, physical environment, economic conditions, health and wellbeing, and individual characteristics.MethodsConfirmatory factor analysis was used to validate both models. While both models demonstrated strong and consistent goodness-of-fit measures, the findings reveal that the 4-factor model outperforms the 5-factor model.ResultsOur findings suggest that the 4-factor model provides a good fit to the modified model and reduces the risk of redundancy and overfitting in evaluating the factors that impact student success.DiscussionBased on our findings, we advocate for academic institutions to adopt the HESF model to identify better where students need support, ultimately improving university completion rates in Australia.